Managing the Margins: Gender, Citizenship, and the International Regulation of Precarious Employment - Artemova, Olga (Relations industrielles / Industrial Relations, 2012)
The article reviews the book, "Managing the Margins: Gender, Citizenship, and the International Regulation of Precarious Employment," by Leah F. Vosko.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment practices; LABOR market; Labor Unions; Regulation; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z